2015
DOI: 10.1111/jpn.12430
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of manganese from manganese–lysine complex in the primary rat intestinal epithelial cells

Abstract: This study was conducted to compare the differences of the uptake of Mn from Mn-lysine complex (MnLys) and MnSO and to determine the potential mechanisms of the uptake of Mn from MnLys. We first established the primary rat intestinal epithelial cell culture model and used it to determine the uptake of Mn from different Mn sources. The MnLys increased (p < 0.001) Mn uptake when compared to MnSO . The uptake of Mn decreased (p < 0.05) with added Fe concentration increasing in the medium regardless of Mn source. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Although Nockels et al (1993) observed decreases in Zn absorption during stress, no difference in absorption was observed between different sources of Zn (ZS and Zn-Met). The lower retention of Zn from ZG as compared with ZAA might be true based on the theory that trace minerals bound to amino acids are absorbed into the enterocyte via amino acids transport system vs. transporters such as ZIP4 ( Gao et al, 2014 ; Sauer et al, 2017 ; Zhang et al, 2017 ) and that Gly is less efficiently absorbed than other amino acids ( Gardner, 1976 ; Reichl, 1989 ). Further research is needed to explore differences in Zn metabolism among Zn sources as affected by factors such as stress, animal type (monogastric vs. ruminant), and ligand.…”
Section: Discussionmentioning
confidence: 99%
“…Although Nockels et al (1993) observed decreases in Zn absorption during stress, no difference in absorption was observed between different sources of Zn (ZS and Zn-Met). The lower retention of Zn from ZG as compared with ZAA might be true based on the theory that trace minerals bound to amino acids are absorbed into the enterocyte via amino acids transport system vs. transporters such as ZIP4 ( Gao et al, 2014 ; Sauer et al, 2017 ; Zhang et al, 2017 ) and that Gly is less efficiently absorbed than other amino acids ( Gardner, 1976 ; Reichl, 1989 ). Further research is needed to explore differences in Zn metabolism among Zn sources as affected by factors such as stress, animal type (monogastric vs. ruminant), and ligand.…”
Section: Discussionmentioning
confidence: 99%
“…And then chicken IECs proliferated to a monolayer of cuboidal cells at 3–4 days post-seeding. The morphological characteristics of chicken IECs were similar to the primary rat IECs but the time for forming confluence monolayer was earlier in primary chicken IECs than in primary rat IECs [33]. The presence of cytokeratin-18, an intermediate cytoskeletal filament that traverses the cell cytoplasm, is characteristic of IECs [37], and vimentin is an intermediate filament specific for intestinal fibroblast [40].…”
Section: Discussionmentioning
confidence: 99%
“…Through this method, cells were assessed for the presence of cobblestone morphology, crypts, and the degree of fibroblast contamination. Cytokeratin-18 (an intermediate filament specific for epithelial cells) and vimentin (an intermediate filament specific for mesenchymal cells such as intestinal fibroblast) were visualized by IF staining [33]. Cells were fixed with ice-cold methanol for 15 min, subsequently washed with PBST (PBS plus 0.05% Tween 20), and blocked for 45 min with 5% skim milk powder at room temperature (RT).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many trace metals such as zinc, manganese, copper ions can be transported into the cells as free ions or transported as a complex with amino acids such as histidine, lysine and methionine through amino acid transporters. [14][15][16][17][18][19][20][21] The uptake rate via these two mechanisms are however different. 22 Amino acid concentration in the medium can thus affect the bioavailability and toxicity of trace metals.…”
Section: Introductionmentioning
confidence: 99%